Cancer in Young Adults With Ischemic Stroke. Issue 6 (June 2015) - Aarnio, Karoliina; Joensuu, Heikki; Haapaniemi, Elena; Melkas, Susanna; Kaste, Markku; Tatlisumak, Turgut; Putaala, Jukka
Abstract : Background and Purpose—: Cancer is a risk factor for ischemic stroke. Little is known about cancer among young adults with ischemic stroke. We studied the frequency of cancer and its association with long-term risk of death among young patients with first-ever ischemic stroke. Methods—: 1002 patients aged 15 to 49 years, registered in the Helsinki Young Stroke Registry, and with a median follow-up of 10.0 years (interquartile range 6.5–13.8) after stroke were included. Historical and follow-up data were derived from the Finnish Care Register and Statistics Finland. Survival between groups was compared with the Kaplan–Meier life-table method, and Cox proportional hazard models were used to identify factors associated with mortality. Results—: One or more cancer diagnosis was made in 77 (7.7%) patients, of whom 39 (3.9%) had cancer diagnosed prestroke. During the poststroke follow-up, 41 (53.2%) of the cancer patients died. Median time from prestroke cancer to stroke was 4.9 (1.0–9.5) years and from stroke to poststroke cancer was 6.7 (2.7–10.9) years. Poststroke cancer was associated with age >40 years, heavy drinking, and cigarette smoking. The cumulative mortality was significantly higher among the cancer patients (68.6%, 95% confidence interval 52.0%–85.3%) compared with patients without cancer (19.7%, 95% confidence interval 16.3%–23.2%). Active cancer at index stroke, melanoma, and lung/respiratory tract cancer had the strongest independent association with death during the follow-up when adjusted for known poststroke mortality prognosticators. Conclusions—: Cancer, and especially active cancer and no other apparent cause for stroke, is associated with unfavorable survival among young stroke patients. Abstract : Supplemental Digital Content is available in the text.